CURRÍCULO E LINGUAGEM: PERSPECTIVAS E POSSIBILIDADES DE ENSINO DE LÍNGUA PORTUGUESA - Antunes, Ciro Carlos (Revista Ciranda, 2024)
The text highlights the importance of integrating knowledge and expression in educational development, particularly through the teaching of the Portuguese language. Technological advancements have accelerated the school curriculum but have also increased social disparities, hindering access to education. In Brazil, Portuguese language teaching faces challenges in democratizing education. The quality of language instruction is linked to the effectiveness of the study program and the pedagogical approach. The study emphasizes the need to understand and reinterpret different textual types in order to act effectively in social contexts. The research adopted an exploratory qualitative approach, using bibliographic methods. The results indicate that the study and expression program permeates the educational system, guiding the content and purpose of the school. This program encompasses the curriculum content and pedagogical approach, including learning through textual types and genres, addressing challenges related to the use of technological resources in language teaching. It is concluded that the program plays a crucial role in cultivating learning skills by promoting the importance of reading, writing, and competence in everyday and professional life.